Impacts of Covid-19 on Supply Chain and Business Operations on Enterprises in the Province of Ilocos Norte - Eric S Parilla; Marc Edward Abadilla (Logistic and Operation Management Research (LOMR), 2022)
The study investigates the effects of the pandemic brought about by Covid-19 on Ilocos businesses and establishments on its business operations and supply chain. The study participants were the 352 owners of the micro, small, medium, and large businesses in Ilocos Norte, and they were selected using a convenience sampling technique. The study employed a quantitative research design, and the entrepreneurs were asked about the perceived impact of Covid-19 on the supply chain. Using descriptive statistics, the findings divulged that the impact of the Covid-19 pandemic on the businesses ranged from retrenchment of employees, disruption in the supply chain, and temporary to permanent shutdown. The impact of the pandemic includes uncertainties, the decline in productivity, demand, and sales. This study implies that COVID-19 significantly affects operations, primarily supply chain management. Numerous organizations are pursuing local sourcing as a result of supply chain disruptions.